Effects of cashless payment towards corruption in Malaysia Thailand and Singapore - Low, Ai Chin; Lyydea Abryna Clive, Clive; Tan, Zheng Kai; Vinitha, Krishnan (2020)
Corruption happens due to untraceable financial transactions. Therefore, the purpose of carrying out this study is to find out the relationship between corruption and cashless payment, which can be detected than physical cash transactions in Malaysia, Thailand, and Singapore. Based on the decision, we planned to determine the effect of each type of cashless payment on corruption. The types of instruments are cheques, direct debit, card, and e-money. Besides that, we also implement economic prosperity, government size, democracy, and income inequality as our independent variables. We also presented 10-year data from 2007 to 2017 from Freedom House, WID, World development indicators, and included 3 countries which are Malaysia, Thailand, and Singapore in our research. Firstly, we generate descriptive statistics in this study to review each variable in a separate country for Singapore, Malaysia, and Thailand. Before we start the OLS regression we carry on the Unit Root Test. The test is used to make sure our model is stationary; ADF and PP tests are conducted. We found out that in Singapore, all variable is stationary at second difference while for Malaysia and Thailand variables are stationary at first difference. Then we continue our test in the OLS test and found that in Singapore, GDP and cheque cashless payments have a positive relationship to corruption, while other variables are a negative relationship with corruption.